To the Evolutionary Conceptions of Organization’s Management (UNWE Yearbook, 2009)
:The study has an object to suggest foundations of a possible contemporary methodological approach and methodical instruments for applying the evolutionary standpoint to the management science and practice. Various aspects in which that standpoint fins expression in classical management conceptions of the organizational changes are viewed. Fundamental formulations of the evolutionary transformations of the chaos philosophy and theory are represented. On that basis an attempt is made to formulate fundamental postulates of the management evolutionary conception and to interpret them by a methodological scheme of threats to the organizations localization, measurement and evaluation as well as of generation and evaluation versions of their limitation.Methods for the threats to organization measurement are elaborated that to provide first step to achievement of the primary organization aim of homeostasis/survival. The methods are described by its instruments, limiting conditions, stages and procedures and some results of their approbation. Basic instruments of the methods are method of focus groups, investigation method by questionnaires, paired comparison method and calculus by confidential intervals. The methods are approbated for the University of National and World Economy (UNWE). Results for the licensing institution “students” of the UNWE are represented in the study. These are aggression functions and present aggression evaluations of the licensing institution “students” as well as functions of threat to the UNWE and licensing table of threats of that licensing institution to the UNWE.